Talimogene laherparepvec: first-in-class oncolytic immunotherapy - Harrington, Kevin (Henry Stewart Talks, 2016)
Causing tumour cell lysis, Initiating a specific systemic immune response, T-VEC as an oncolytic HSV-1 strain, Assessing cancer immunotherapy through melanoma, Applicability of oncolytic viral therapy to various cancers